MODEL KOLABORASI GURU PENDIDIKAN AGAMA ISLAM DAN GURU BIMBINGAN KONSELING DALAM MENGATASI PERILAKU NEGATIF SISWA DI SMPIT AR-RAHMAN JAKARTA SELATAN - Mochamad Daffa Akmal; Ummah Karimah; Siti Shofiyah (Institut Daarul Qur'an Jakarta, Indonesia, 2026)
Islamic education places significant emphasis on moral formation, positioning morality as the foundation of character development. Addressing negative behavior in adolescents requires an integrative educational approach that combines spiritual, behavioral, and psychological guidance. This study aims to formulate a collaborative model between Islamic Education (PAI) teachers and Guidance and Counseling (BK) teachers in addressing negative student behavior in Islamic-based junior high schools. Different from previous research that discussed the role of teachers separately, the novelty of this research lies in the formulation of an integrative collaboration model between Islamic Religious Education teachers and Guidance and Counseling teachers which is based on preventive, repressive, and curative strategies within a framework for developing students' morals in integrated Islamic schools. Unlike previous studies that separate religious-educational and counseling roles, this research presents a structured and integrated collaboration framework organized into preventive, repressive, and curative strategies. Using a qualitative case study design, data were collected through in-depth interviews, observations, and documentation involving one PAI teacher, one BK teacher, and two students at SMPIT Ar-Rahman, South Jakarta. Data were validated using triangulation and analyzed through Miles and Huberman’s interactive model. Findings reveal seven core methods of moral education: exemplary, habituation, advice, Islamic storytelling, motivation, discipline, and educative punishment. These methods are strengthened by school-wide religious programs including morning dhikr, dhuha prayer, congregational prayers, mentoring, PHBI, courtesy culture, and ruhiyah week. This study contributes a new integrative collaboration model for Islamic schools that can effectively reduce negative behaviors and enhance moral internalization among students.